Analysis of Broiler Chicken Farming Business Income in Partner Patterns in Muaro Sentajo Village, Sentajo Raya District, Kuantan Singingi Regency (Case Study of Mrs. Suniati's Livestock Business) - Romauli Romauli; Meli Sasmi; Mashadi Mashadi (Baselang, 2021)
The purpose of this research is to find out how much the cost, income, efficiency and Break Event Point for the broiler chicken breeder business partner Mrs. Suniati in Muaro Sentajo Village, Sentajo Raya District, Kuantan Singingi Regency. To analyze the data used mathematical analysis with descriptive and quantitative analysis. This research is a case study research in which research is focused on only one broiler chicken farming business. Results for analyzing revenues, costs and production are analyzed once in the production process. The results of this study indicate that Ibu Suniati's partner broiler chicken pattern with a scale of 3000 tails uses a cost of Rp.79,200,323, - / period, the receipt is Rp.81,154,080 /, - period, with a total profit of Rp.1,953. 757 / period, and an efficiency level of Rp. 1,025 / period which means 1 rupiah of the cost incurred then obtains revenue of 1,025 rupiahs or a profit of 0.25 rupiahs. And the level of Break Event Point in this study is that the production BEP is 4,342 kg, where the broiler breeder, the partner pattern of Ibu Suniati, must produce broiler chickens above 4,342 kg, while the price for the BEP is Rp. 18.136, - means that this broiler breeder, Ibu Suniati's partner pattern, must sell at a price of Rp. 18,136.